The Development of Canva-Based Animated Videos to Improve Critical Thinking Skills of Elementary/Islamic Elementary School Students in Science Classes on Human Digestive System Materials - Hilmiyati, Fitri; Nafsi, Agni Gina; Sabri, Sabri (Al-Aulad: Journal of Islamic Primary Education, 2024)
The background of this research is the lack of interactive learning media that can stimulate critical thinking learning, and the difficulty of teachers in developing IT-based learning media. The research objective was to determine the development and feasibility procedures of Canva-based animated video media to improve critical thinking skills in science lessons. The method used in this research is Research and Development (R&D) with the ADDIE research model, which consists of 5 stages, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. Based on the steps above, the researchers produced a product in the form of an animated video based on Canva in natural science lessons on the human digestive system. From the data obtained after the feasibility test results were validated by media experts and material experts with an overall validator score of 93.74% in the "very feasible" category. Furthermore, the results of the pre-test and post-test showed an increase of 38.48, which means that the designed media has an effect on student learning outcomes. Then increase students critical thinking skills with a result of 0.8 with "high" category. So, it can be concluded that Canva-based animated video media is feasible to use and can improve critical thinking skills.